Biomass-derived carbon material as efficient electrocatalysts for the oxygen reduction reaction. (January 2023) - Cao, Yue; Sun, Yegeng; Zheng, Runtian; Wang, Qing; Li, Xue; Wei, Haoran; Wang, Likai; Li, Zhongfang; Wang, Fagang; Han, Ning
Abstract: Despite the abundance of carbon in nature, a significant portion of the existing biomass carbon materials in livestock, agriculture, and marine fishery industry are currently being wasted. Utilizing sustainable carbon materials as an alternative to noble Pt-based catalysts is crucial step to convert widely available and low-cost biomass resources into clean energy systems. Therefore, the rational synthesis of carbon-based catalysts for oxygen reduction reaction (ORR) has become a hot research focus in the field of electrochemistry. In this study, the recent progress in the synthesis of ORR electrocatalysts using sustainable biomass resources was reviewed; the activation and synthesis strategies of various biomass resources, as well as the microstructure and oxygen reduction performance of the prepared carbon-based catalysts were investigated. It is hoped that this review article will promote the understanding of various parameters from biomass as precursors for catalyst preparation and make contribute to the transition of biomass resources from the wasted carbon materials to the main catalysts in future energy devices. Graphical abstract: Image 1 Highlights: The synthesis and activation strategy of biomass-derived carbon. Effect of pore structure on activity of ORR catalysts. Recent progress biomass-derived carbon material as ORR catalysts.